New Insights on CD8+ T Cells in Inflammatory Bowel Disease and Therapeutic Approaches - Casalegno Garduño, Rosaely; Däbritz, Jan (Frontiers in Immunology, 2021)
CD8+ T cells are involved in the pathogenesis of inflammatory bowel disease (IBD), a complex multifactorial chronic disease. Here, we present an overview of the current research with the controversial findings of CD8+ T cell subsets and discuss some possible perspectives on their therapeutic value in IBD. Studies on the role of CD8+ T cells in IBD have contradictory outcomes, which might be related to the heterogeneity of the cells. Recent data suggest that cytotoxic CD8+ T cells (Tc1) and interleukin (IL) 17-producing CD8+ (Tc17) cells contribute to the pathogenesis of IBD. Moreover, subsets of regulatory CD8+ T cells are abundant on sites of inflammation and can exhibit pro-inflammatory features. Some subsets of tissue resident memory CD8+ T cells (Trm) might be immunosuppressant, whereas others might be pro-inflammatory. Lastly, exhausted T cells might indicate a positive outcome for patients. The function and plasticity of different subsets of CD8+ T cells in health and IBD remain to be further investigated in a challenging field due to the limited availability of mucosal samples and adequate controls.